A velhice e suas possibilidades de sentidos : uma análise de narrativas e imaginário social - Souza, Antônio de Castro (2022)
Old age is a phase of changes in routine, health, appearance and perception of oneself and the world. And it is revealed to many as a stigma, a fact that draws our attention to the need to deepen investigations on the subject. The literature that deals with the subject of old age, sometimes, goes on silently amidst many other themes that are said to be of greater relevance. In order to break this silence or promote debate, our investigation seeks to identify and reflect on the meanings that old age acquires in narratives, those that mainly try to name or define it. At first, we seek to explore the nuances of what we call old age, as well as problematize the attempt to conceptualize it. In this sense, we consider, in this dissertation, Beauvoir's understanding of the non-generalization of old age, with its particularities according to each person, culture and time. To support the perspective of old age that we adopted, we will approach Beauvoir's studies, contextualizing old age, mainly in society, together with its meanings throughout the history of humanity. Based on the understanding elaborated in this dissertation, we will also approach old age in the current discourse; and we also use the scientific productions of the main areas of studies that are dedicated to researching old age: the Psychology of Aging, Geriatrics and Gerontology. Such reflections open the way for us to think about the relevance given to research on old age, which does not fail to provide, also, meanings to be captured and (de)constructed according to the reading. Instigated by the existence of a dominant discourse — the medical discourse —, in the next chapter, we cover a characteristic of today's society that mainly affects the old of our times: the generalized medicalization of life. And, finally, we direct the work to the relationship between old age and death, highlighting an element that unites these two aspects of life: concealment. We conclude, then, that both meanings highlighted in the research have been pointing to a place: the non-social place; that is, the elderly are increasingly losing their place and voice in society. The study also corroborates Beauvoir's defense that there is not only one old age, but multiple ways of experiencing aging. That is, multiple senses; each person living the uniqueness of this experience, rearticulating and giving new meaning according to subjectivation processes, such as the aging described by Berlink (2000) and Soares (2005); or even through sublimation, as defended by Mucida (2019).